2021
DOI: 10.14309/ctg.0000000000000290
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Risk Score Performance of Hepatocellular Carcinoma Development in Patients With Hepatitis B Surface Antigen Seroclearance

Abstract: INTRODUCTION: Hepatocellular carcinoma (HCC) can develop among chronic hepatitis B patients after hepatitis B surface antigen (HBsAg) seroclearance. However, whether HCC risk after HBsAg seroclearance differs between antiviral therapy (AVT)-induced or spontaneous seroclearance cases and ways to identify at-risk populations remain unclear. METHODS: A retrospective cohort of 1,200 adult chronic hepatitis B patients who achieved HBsAg seroclearance (median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
10
0
2
Order By: Relevance
“…HBsAg seroclearance is also achieved in a few patients on antiviral treatment, and the long-term clinical outcome compared with that of spontaneous HBsAg seroclearance is unclear [ 45 , 46 ]. Two studies showed no difference in HCC incidence between patients who achieved treatment-induced and spontaneous HBsAg seroclearance [ 47 , 48 ], yet another study reported a 5-year cumulative incidence of HCC of 0.9% and 3.9% in spontaneous and treatment-induced HBsAg seroclearance patients, respectively [ 49 ].…”
Section: Natural Historymentioning
confidence: 99%
“…HBsAg seroclearance is also achieved in a few patients on antiviral treatment, and the long-term clinical outcome compared with that of spontaneous HBsAg seroclearance is unclear [ 45 , 46 ]. Two studies showed no difference in HCC incidence between patients who achieved treatment-induced and spontaneous HBsAg seroclearance [ 47 , 48 ], yet another study reported a 5-year cumulative incidence of HCC of 0.9% and 3.9% in spontaneous and treatment-induced HBsAg seroclearance patients, respectively [ 49 ].…”
Section: Natural Historymentioning
confidence: 99%
“…The baseline characteristics are provided in Table 1. Among the 57 studies, 2 were prospective population‐based studies, 11,12 22 were prospective 8,9,13‐32 and 33 were retrospective cohort studies 7,33‐64 . Overall, there were a total of 258 744 HBsAg positive patients of whom 63 270 (24.4%) lost HBsAg.…”
Section: Resultsmentioning
confidence: 99%
“…7 Though the risk has been significantly lowered by effective antiviral therapy, it cannot be eliminated. [3][4][5]18 Even, the incidence of HCC in these patients is still higher than that in inactive-stage CHB patients. 19,20 In our study, the 36-month cumulative incidence of HCC was 1.4% in CHB patients on antiviral therapies, 0.5% in chronic carriers and 1.0% in total.…”
Section: Discussionmentioning
confidence: 95%
“…patients with more than 5 years of effective entecavir treatment 3 or with hepatitis B surface antigen (HBsAg) loss. 4,5 Thus, all the guidelines recommend HCC surveillance in chronic HBV-infected patients routinely and regularly. 2,[6][7][8][9] The Asian Pacific Association for the Study of the Liver (APASL) even suggests regular surveillance in patients who lost HBsAg.…”
mentioning
confidence: 99%